Design of a solar energy harvesting system for supplying energy to an autonomous wireless sensor node - Salazar Cardona, Mónica María; Marulanda Tobón, Alejandro (Ingeniería Solidaria, 2021)
Introduction: This paper is the product of the research “Generation of a modular electronic platform for the conformation of a WSN” developed in the EAFIT University in 2019.Problem: Wireless Sensor Networks (WSNs) are used as a technology of information and communication (TIC) to automate processes. Its implementation is considered non-efficient, because of their high cost concerning to the batteries replacement that the nodes conforming the WSN, require.Objective: The objective of the research is to develop more efficient solar energy harvesting systems that can guarantee an average performance of the wireless sensor node at a low cost.Methodology: Here we present the design and the implementation of a solar energy harvesting system that integrates a buck converter, a maximum power point tracking (MPPT) control, and a wireless sensor node. Besides, we do measures of voltage at the output of the buck converter and estimation of energy autonomy in the wireless sensor node.Results: Autonomous operation with the solar energy harvesting system was rich for the node sending packages each 20 min.Conclusion: This article presented a solar energy harvesting system with the implementation of an MPPT control.Originality: Through this research, parameters of the MPPT control are formulated for the first time for the solar energy harvesting system design, based on the duty cycle limits.Limitations: The availability of the devices used in the implementation of the proposed design.